CONSIDERATIONS REGARDING THE OPERATION OF MILITARY POLICE, AS AN INTEGRAL PART OF THE JUDICIARY - Lazau-Pacuraru, Atanasie (International Journal of Legal and Social Order, 2021)
Judicial safeguards are particularly important and regulated in detail as fundamental human rights, in proceedings brought before domestic, as well as international criminal courts, with pertinent provisions being established as to the legality of the crime and of punishments. At present, in the series of specialized conferences with a role in highlighting the importance of implementing the concept of “need for high social capital”, it is emphasized that the application of the principles of criminal proceedings provides the foundation for citizen protection as an integral part of public safety, the entire edifice of criminal procedure rules being built on these principles. Basically, the need for social security offered through the activity of forensic investigation of criminal offences cannot be dispersed among disciplines auxiliary to forensic science without the major contribution of criminal law.